Proceedings of SPE Asia Pacific Oil and Gas Conference and Exhibition 1998
DOI: 10.2523/50079-ms
|View full text |Cite
|
Sign up to set email alerts
|

Planning, Execution and Lessons Learned From the GWA13 Extended Reach Drilling Well - Goodwyn Gas/Condensate Field, NWS, Australia

Abstract: GWA13 was the last well during Phase 1 of the development of the Goodwyn field and was drilled to a total depth of 8420m (27620') AHD with a horizontal step out of 7372m (24190') at a TVD of 2866m (9400'). The paper describes the planning processes before spud, and the equipment, techniques and directional control used during the drilling phase. Lessons that can be applied to both our own and other operations will be listed. The team approach to the drilling of Goodwyn wells will be emphasised and the risk ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Extended Reach Drilling (ERD) is a technique to drill directional/horizontal wells beyond the routine capabilities of drilling rigs and tools. ERD was initiated in 1980's and rapidly evolved during the 1990's [1][2][3][4]. Naegel et al [5] reported an ERD well with a 20,341.2 ft horizontal departure at 5,577 ft true vertical depth (TVD).…”
Section: Introductionmentioning
confidence: 99%
“…Extended Reach Drilling (ERD) is a technique to drill directional/horizontal wells beyond the routine capabilities of drilling rigs and tools. ERD was initiated in 1980's and rapidly evolved during the 1990's [1][2][3][4]. Naegel et al [5] reported an ERD well with a 20,341.2 ft horizontal departure at 5,577 ft true vertical depth (TVD).…”
Section: Introductionmentioning
confidence: 99%